2005
DOI: 10.1063/1.1856891
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect of La0.8Sr0.2MnO3 compound under pressure

Abstract: The La0.8Sr0.2MnO3 compound presents a ferromagnetic paramagnetic transition around room temperature to which a reasonably high magnetocaloric effect is associated, turning this material of interest for application in magnetic refrigeration. We synthesized this compound in fiber single crystalline form by the Laser Heated Pedestal Growth method. The sample was characterized by x-ray diffraction and magnetic measurements as a single phase and with the required magnetic properties. We measured the magnetic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…There is also a first-order phase transition in MnAs under hydrostatic pressure [8]. When subjected to pressure, similar large MCE was found in Gd 5 Ge 2 Si 2 [9], La 0.8 Sr 0.2 MnO 3 [10] and La(Fe 1 À x Si x ) 13 H y [11] assisted by magnetoelastic interactions. Specifically, bulk MnAs undergoes a magnetic transition from a ferromagnetic (FM) phase to a paramagnetic (PM) phase at T c = 313 K, accompanied by a structural transition from hexagonal NiAs-type to orthorhombic MnP-type [12].…”
Section: Introductionsupporting
confidence: 67%
“…There is also a first-order phase transition in MnAs under hydrostatic pressure [8]. When subjected to pressure, similar large MCE was found in Gd 5 Ge 2 Si 2 [9], La 0.8 Sr 0.2 MnO 3 [10] and La(Fe 1 À x Si x ) 13 H y [11] assisted by magnetoelastic interactions. Specifically, bulk MnAs undergoes a magnetic transition from a ferromagnetic (FM) phase to a paramagnetic (PM) phase at T c = 313 K, accompanied by a structural transition from hexagonal NiAs-type to orthorhombic MnP-type [12].…”
Section: Introductionsupporting
confidence: 67%
“…which is higher than that found measuring amorphous LSMO powder of the same composition, T C ≈ 305 K [23]. In (b), the results of MTGA in the temperature range 300 K < T < 470 K are shown with an applied magnetic field of 0.1 T. When the sample changes from the paramagnetic to ferromagnetic state, the experienced magnetic force counteracts the gravity of the sample mass.…”
Section: Magnetization Datamentioning
confidence: 80%
“…At 9.2 GPa, a single broad peak is observed at 550 cm 1 . The intense peak might be considered as either due to the merging of 3 and 4 or due to the vanishing of 4 with the increment in 3 . Associating the result with Mössbauer and HPXRD measurements, the presence of the nanoparticles along with the single phase composition at this high pressure strongly recommends the former option.…”
Section: Raman Analysis At High Pressuresmentioning
confidence: 99%
“…Although there are reports of temperature-induced structural changes, 2 very few studies have been reported on the high-pressure behavior of these compounds. 3 -5 A continuous decrease in the Jahn-Teller distortion with increase in pressure in LaMnO 3 and La x Sr 2 x MnO 4 has been reported. 6,7 Doping with Fe at Mn site dilutes the Jahn-Teller atoms, giving a series of double-exchange ferromagnets of decreasing transfer carrier concentration.…”
Section: Introductionmentioning
confidence: 99%